An outline of innovation management process: building a framework for managers to implement innovation - VAYVAY, ÖZALP; KALENDER, ZEYNEP TUĞÇE (ELSEVIER SCIENCE BV, 2014)
Innovation management emerged as a discipline in the 1890's with Edison's innovation factory. Edison changed the image of the sole inventor by converting innovation to a process with recognized steps practiced by a team of inventors working together-laying the basic design of the R&D department. These steps are streamlined to the major extent in all industries and include idea generation, concept development, feasibility studies, product development, market testing and launch. Innovation management is thus corresponds to the development of new products, processes and services. In cases where the organization does not make or offer products (goods or services), innovation lies in improving the way jobs are done to meet the organization's mission. This study will outline the general terms related to innovation and how it is evolved through years based on the literature review. Since market demands differ during the time and awareness of the customer increases, companies increased the bar for competencies. This framework starts with the need or problem definition and outlines different techniques to evolve the ideas. In the real life case study, Generator Rewind process is investigated in detail and the core problem is defined. Innovation management process tools are simplified the complex problem and reveals the core problem and basic needs so team members just follow the innovation management process step by step which is determined and investigated before. After that, in order to develop all possible solutions, an engineering team gathered and performed idea generation and developing meetings to find the best solutions. By implementing TRIZ methodology, the team achieved single and lightweight pieces as an innovation for rotor field winding services. Crown Copyright (C) 2014 Published by Elsevier Ltd.
Keywords: Innovation management process; Innovartion types and models; Poor innovation management; PRODUCT INNOVATION